Knowledge and Awareness Among Dental Students Regarding Carcinoma of Maxillary Sinus - MANOHAR, JANHVI; GANAPATHY, DHANRAJ; PANDURANGAN, KIRAN KUMAR; VELAYUDHAN, ASHOK (The journal of contemporary issues in business and government, 2020)
Maxillary sinus malignancies are rare worldwide. The disease usually presents at an advanced stage making its management challenging for all the medical personnel involved in its treatment. Because of its location deep within the maxilla and its proximity to critical surrounding structures, radiotherapy plays an integral role in sterilizing the area of malignant cells. Sinonasal malignancies occur twice as often in males as in females, and are most often diagnosed in patients 50 to 70 years of age. Maxillary sinus carcinomas are aggressive in nature which present with symptoms in the advanced stages when radical resection becomes the only choice. It is essential to study the basis of such carcinomas and create awareness among patients and dental students to ensure early diagnosis and therefore a good prognosis. A questionnaire based study was conducted among dental students of third, fourth year and interns at a private dental college in Chennai, Tamilnadu, India to assess their knowledge and understanding of carcinomas of maxillary sinus. A multiple choice questionnaire was presented to 103 subjects and their responses were noted, tabulated and statistical analysis was performed using SPSS by IBM by performing Chi-square test. Among 103 subjects, 28 were third year students (27.2%), 47 were interns (45.6%) and remaining 28 of the subjects were fourth year students Fourth year students had increased awareness about carcinomas of maxillary sinus when compared to third year students and interns in most cases (p>0.05).